Experimental investigation of Fe3+-rich majoritic garnet and its effect on majorite geobarometer. (15th March 2018) - Tao, Renbiao; Fei, Yingwei; Bullock, Emma S.; Xu, Cheng; Zhang, Lifei
Abstract: Majoritic garnet [(Ca, Mg, Fe 2+ )3 (Fe 3+, Al, Si)2 (SiO4 )3 ] is one of the predominant and important constituents of upper mantle peridotite and ultra-deep subducted slabs. Majoritic substitution in garnet depends on pressure, and it has been used to estimate the formation pressure of natural majoritic garnet. Ferric iron (Fe 3+ ) substitution occurs in natural majoritic garnets from mantle diamonds and shocked meteorites. However, available majorite geobarometers were developed without considering the effect of Fe 3+ substitution in the structure. In this study, we systematically synthesized Fe 3+ - bearing majoritic garnets from 6.5 GPa to 15 GPa to evaluate the effect of Fe 3+ on the majorite geobarometer. The Fe 3+ contents of synthetic majoritic garnets were analyzed using the "Flank method" with the electron probe microanalyzer (EPMA). The results were compared with those based on the charge balance calculations. From the known synthesis pressures and measured Fe 3+ contents, we developed a new majorite geobarometer for Fe 3+ -bearing majoritic garnets. Our results show that the existing majorite geobarometer, which does not take into account the Fe 3+ substitution, could underestimate the formation pressure of majoritic garnets, especially for samples with a high majoritic component.